The impact of transport energy consumption and foreign direct investment on CO2 emissions in ASEAN countries - Shabir, Mohsin; Gill, Abid Rashid; Ali, Minhaj (Frontiers in Energy Research, 2022)
The current study assesses the impact of foreign direct investment (FDI) and energy consumption of the transport sector on CO2 emission in selected five ASEAN countries using the environment Kuznets curve (EKC) framework for the period 1980-2019. The study uses a Non-linear Autoregressive Distributive Lag Model (NARDL) for the analysis of the data. The results suggest that CO2 emission and its determinants have a long-run equilibrium cointegrated relationship. The EKC relation between income and CO2 emissions holds only for Singapore, while for Indonesia, Malaysia, Philippines, and Thailand, income growth positively impacts CO2 emission. FDI and energy consumption in the transport sector also have a significant positive impact on CO2 emission for selected five ASEAN countries except for Singapore. Transport energy consumption contributes more than FDI to CO2 emissions. Moreover, results also suggest that FDI and energy consumption-led growth models are relevant for ASEAN economies. The study recommends cautious growth policies, clean FDI inflows, and an emphasis on energy-efficient transport systems.